Intestinal Microbes, Metabolites, and Hormones in Alcohol-Associated Liver Disease - Wang, Ruimeng; Ma, Fang; Yin, Dou; Wang, Hua; Wei, Xiaohui (Seminars in Liver Disease, 2025)
Alcohol-associated liver disease (ALD)—encompassing conditions including steatosis, fibrosis, cirrhosis, and hepatocellular carcinoma—refers to hepatic damage arising from excessive or hazardous alcohol consumption, and is now recognized as a significant global health burden. Although the mechanisms underlying ALD remain incompletely understood, several pathways have been substantiated over the last five decades, notably the involvement of intestinal microorganisms and the involvement of the gut–liver axis in alcohol metabolism and ALD pathogenesis. Ethanol intake disrupts the intestinal microbial balance and compromises the gut barrier, resulting in increased permeability to microbial products. The subsequent translocation of microbial metabolites and other antigenic substances to the liver activates hepatic immune responses, thereby contributing to liver injury. In addition, gastrointestinal hormones are also implicated in ALD progression through various mechanisms. Although no therapies for ALD have been approved by the Food and Drug Administration, various therapeutic strategies targeting the intestinal microbiota and gut barrier have been identified. In conclusion, this review discusses the role of the gut–liver axis in alcohol metabolism and ALD pathogenesis and explores the emerging therapeutic strategies.
Keywords: alcohol-associated liver disease; bacterial products; gastrointestinal hormones; microbial therapy